Knockdown of miR-361-5p promotes the induced activation of SHF-stem cells through FOXM1 mediated Wnt/β-catenin pathway in cashmere goats - Ruqing Xu; Man Bai; Yixing Fan; Yubo Zhu; Zeying Wang; Taiyu Hui; Qi Zhang; Xingwang Liu; Jialiang Zhang; Jincheng Shen; Wenlin Bai (Animal Biotechnology, 2024)
The inducing activation event of secondary hair follicle (SHF)-stem cells is considered a key biological process in the SHF regeneration, and the morphogenesis of cashmere fiber in cashmere goats. The miR-361-5p was essentially implicated in the induced activation of SHF-stem cells of cashmere goats, but its functional mechanisms are unclear. Here, we confirmed miR-361-5p was significantly downregulated in anagen SHF bugle of cashmere goats compared with that at telogen, and miR-361-5p expression was significantly lower in SHF-stem cells after activation than its counterpart before activation. Further, we found that miR-361-5p could negatively regulate the induced activation event of SHF-stem cells in cashmere goats. Mechanistically, through dual-luciferase reporter assays, miR-361-5p specifically bound with FOXM1 mRNA in SHF-stem cells of cashmere goats and negatively regulated the expression of FOXM1 gene. Also, through overexpression/knockdown analysis of FOXM1 gene, our results indicated that FOXM1 upregulated the expression of Wnt/β-catenin pathway related genes in SHF-stem cells. Moreover, based on TOP/FOP-flash Wnt report assays, the knockdown of miR-361-5p promotes the Wnt/β-catenin pathway activation through upregulating the FOXM1 expression in SHF-stem cells. Finally, we demonstrated that miR-361-5p negatively regulated the induced activation of SHF-stem cells through FOXM1 mediated Wnt/β-catenin pathway in cashmere goats.